Zhodnocení finanční situace mezinárodně působícího podniku a návrhy na její zlepšení - Zlámalíková, Lucie (Vysoké učení technické v Brně. Fakulta podnikatelská, 2021)
Diplomová práce se zaměřuje na zhodnocení finanční situace vybraného mezinárodně působícího podniku. Práce se skládá celkově ze tří částí, přičemž v teoretické části jsou zmíněny pojmy související s hodnocením finančního zdraví. Analytická část zahrnuje analýzu současného stavu společnosti i trhu. A v poslední části je řešen návrh na zlepšení finanční situace vybrané společnosti.

The diploma thesis focuses on the evaluation of the financial situation of a selected internationally operating company. The work consists of a total of three parts, while the theoretical part mentions concepts related to the assessment of financial health. The analytical part includes an analysis of the current state of the company and the market. And in the last part, a proposal to improve the financial situation of the selected company is addressed.
Evaluation of the Financial Situation of an Internationally Operating Company and Suggestions for its Improvement
Keywords: finanční analýza; poměrové ukazatele; likvidita; zadluženost; devizová rizika; Financial analysis; ratios; liquidity; indebtedness; foreign; exchange risks